2022
DOI: 10.1111/jch.14431
|View full text |Cite
|
Sign up to set email alerts
|

Severe inpatient hypertension prevalence and blood pressure response to antihypertensive treatment

Abstract: Severe hypertension (HTN) that develops during hospitalization is more common than admission for HTN; however, it is poorly studied, and treatment guidelines are lacking. Our goal is to characterize hospitalized patients who develop severe HTN and assess blood pressure (BP) response to treatment. This is a multi‐hospital retrospective cohort study of adults admitted for reasons other than HTN who developed severe HTN. The authors defined severe inpatient HTN as the first documented BP elevation (systolic BP > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…These acute severe BP elevations frequently occur during hospitalization for other reasons. In fact, 10% of nonintensive care unit hospitalized patients, admitted for reasons other than hypertension, have been found to develop incident severe hypertension [ 3 , 4 ]. These high BPs, though often not causing symptoms, usually prompt healthcare providers to administer antihypertensives, commonly intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These acute severe BP elevations frequently occur during hospitalization for other reasons. In fact, 10% of nonintensive care unit hospitalized patients, admitted for reasons other than hypertension, have been found to develop incident severe hypertension [ 3 , 4 ]. These high BPs, though often not causing symptoms, usually prompt healthcare providers to administer antihypertensives, commonly intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that treatment with i.v. antihypertensives was associated with a 38% greater risk (hazard ratio [HR]: 1.38 [1.15, 1.67]) of severe BP reduction (mean arterial pressure reduction of ≥30%) compared to no treatment among inpatients who develop severe hypertension [ 3 ]. However, it is unknown whether treatment of acute severe BP elevation might lead to worse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature examining the immediate effect of BP treatment has documented a potential pathway for the observed harms in which BP immediately declines by greater than 25% over the course of hours, leading to a risk for tissue hypoperfusion. 8,[29][30][31] Intravenous antihypertensives have a greater immediate BP-lowering effect than oral medications, 30 and while both formulations have been associated with immediate BP lowering of greater than 25%, 8 this is more common with intravenous medications, occurring as often as one-third of the time. 31 This association between immediate BP lowering and risk for harms is consistent with our findings of greater risks of adverse outcomes among patients receiving intravenous antihypertensives and an additional observational study of intravenous antihypertensives for severely elevated BPs that found an association with increased risk for myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the use of antihypertensives may result in overly rapid BP lowering, which has been associated with increased risk of cerebral hypoperfusion and death among patients treated for symptomatic hypertensive emergencies. 8,9 Fourth, clinical trials of inpatient diabetes management have demonstrated that applying outpatient treatment targets to inpatient settings may result in overtreatment and harms. 10 Better evidence to inform clinical decision-making is needed to optimize inpatient BP management, particularly for older adults who endure the highest burdens of hypertension, hospitalization, and frailty.…”
mentioning
confidence: 99%
“…We recently found that among patients hospitalized for reasons other than HTN at a large multi-hospital center, severe HTN was prevalent in 10% of patients and 40% received antihypertensive treatment, primarily oral antihypertensives [ 14 ]. Additionally, we report that excessive BP reduction (drop ≥30%) within 6 hours after severe HTN development was observed in treated and untreated patients.…”
Section: Introductionmentioning
confidence: 99%